EFFECT OF OCCUPATIONAL SAFETY AND HEALTH PROGRAM (K3), THE WORK ENVIRONMENT ON THE WORK PROFILES OF EMPLOYEES (Study Of Employees Of The Operational Field Of PT. Karimun Granite) - ", Rosliza; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to find out how much the influence of occupational safety and health programs (K3), the work environment are stunned by employee work productivity (case study of the operational field of PT. Karimun Granite). The sample in this study was taken as many as 70 respondents and the technique used by the census. The data in this study used the survey method through questionnaires filled with employees. Data is obtained using simple regression analysis and multiple regression analysis. The results of this study show that employment safety and health programs (K3) have a significant effect on employee work productivity. And simultaneously occupational safety and health programs (K3) and work environment have a significant effect on employee work productivity. Subsequent research is recommended to use other methods in examining employee work productivity, for example through in-depth interviews for respondents.Â Keywords:.Occupational safety and health programs (K3), work environment, and employee work productivity.Â